2021
DOI: 10.1002/deo2.66
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of colorectal tumors: Differences between Japan and the West and future prospects

Abstract: Dye‐based chromoendoscopy has long been used routinely for endoscopic diagnosis of gastrointestinal tumors including colorectal tumors in Japan. In the West, on the other hand, dye‐based chromoendoscopy was not so commonly used. However, with the development of narrow band imaging (NBI), image‐enhanced endoscopy diagnosis has rapidly increased in the West. The most critical difference between Japan and the West is the histopathological evaluation of the lesions, which determines a major cause of dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…A meta-analysis showed that LST-G-HG has a low probability (0.5%) of SMIC, whereas the LST-G-NM, LST-NG-FE, and LST-NG-PD types have increased risks of SMIC: 10.5%, 4.9%, and 31.6%, respectively [ 9 ]. The risk of SMIC within LSTs increases when large nodules, depressions, or submucosal tumor-like elevations are present [ 20 , 21 ]. It is also important to be cautious about multifocal submucosal invasion.…”
Section: Endoscopic Prediction and Evaluation Of T1 Crcmentioning
confidence: 99%
“…A meta-analysis showed that LST-G-HG has a low probability (0.5%) of SMIC, whereas the LST-G-NM, LST-NG-FE, and LST-NG-PD types have increased risks of SMIC: 10.5%, 4.9%, and 31.6%, respectively [ 9 ]. The risk of SMIC within LSTs increases when large nodules, depressions, or submucosal tumor-like elevations are present [ 20 , 21 ]. It is also important to be cautious about multifocal submucosal invasion.…”
Section: Endoscopic Prediction and Evaluation Of T1 Crcmentioning
confidence: 99%
“…23 In the colon, LST granular type lesions have been shown to have the lowest rate of submucosal invasion, and these can be generally removed by piecemeal EMR with cauterization of the clean margins, in order to decrease the recurrence rate. 24 It was also advised that areas with ulceration (which would be a concern for carcinoma) should be removed in one piece, and not transected as part of a piecemeal resection. Similar to the other areas of the GI tract, larger lesions tend to have higher rates of T1 carcinoma, and EMR for these cases would be less ideal.…”
Section: Is Esd Always Necessary?mentioning
confidence: 99%